Beta-blocker use in severe sepsis and septic shock: a systematic review. (3rd October 2015) - Sanfilippo, Filippo; Santonocito, Cristina; Morelli, Andrea; Foex, Pierre
Abstract: Objective: Recent growing evidence suggests that beta-blocker treatment could improve cardiovascular dynamics and possibly the outcome of patients admitted to intensive care with severe sepsis or septic shock. Design: Systematic review. Data sources: MEDLINE and EMBASE healthcare databases. Review methods: To investigate this topic, we conducted a systematic review of the above databases up to 31 May 2015. Due to the clinical novelty of the subject, we also included non-randomized clinical studies. We focused on the impact of beta-blocker treatment on mortality, also investigating its effects on cardiovascular, immune and metabolic function. Evidence from experimental studies was reviewed as well. Results: From the initial search we selected 10 relevant clinical studies. Five prospective studies (two randomized) assessed the hemodynamic effects of the beta1 -blocker esmolol. Heart rate decreased significantly in all, but the impact on other parameters differed. The imbalance between prospective studies' size (10 to 144 patients) and the differences in their design disfavor a meta-analysis. One retrospective study showed improved hemodynamics combining metoprolol and milrinone in septic patients, and another retrospective study found no association between beta-blocker administration and mortality. We also found three case series. Twenty-one experimental studies evaluated the hemodynamic, immune and/or metabolic effects of selective and/or non-selective beta-blockers in animal models of sepsis (dogs, mice, pigs, rats, sheep), yielding conflicting results. Conclusions: Whilst there is not enough prospective data to conduct a meta-analysis, the available clinical data are promising. We discuss the ability of beta blockade to modulate sepsis-induced alterations at cardiovascular, metabolic, immunologic and coagulation levels.